Oxidative Stress Modulates PPARγ in Vascular Endothelial Cells - Blanquicett, Carmelo (2010)
The peroxisome proliferator-activated receptor gamma (PPARγ) plays an important role in vascular regulation. However, the impact of oxidative stress on PPARγ expression and activity has not been clearly defined. Human umbilical vein endothelial cells (HUVECs) were exposed to graded concentrations of H(2)O(2) for 0.5–72 h, or bovine aortic endothelial cells (BAECs) were exposed to alterations in extracellular thiol/disulfide redox potential (E(h)) of the cysteine (Cys)/cystine (CySS) couple. Within 2 h, H(2)O(2) reduced HUVEC PPARγ mRNA and activity and reduced the expression of two PPARγ-regulated genes without altering PPARγ protein levels. After 4 h H(2)O(2) exposure, mRNA levels remained reduced while PPARγ activity returned to control levels. PPARγ mRNA levels remained depressed for up to 72 h after exposure to H(2)O(2), without any change in PPARγ activity. Catalase prevented H(2)O(2)-induced reductions in PPARγ mRNA and activity. H(2)O(2) 1) reduced luciferase expression in HUVECs transiently transfected with a human PPARγ promoter reporter, 2) failed to alter PPARγ mRNA half-life, and 3) transiently increased expression and activity of c-Fos and phospho-c-Jun. Treatment with the AP-1 inhibitor, curcumin, prevented H(2)O(2)-mediated reductions in PPARγ expression. In addition, media having an oxidized E(h) reduced BAEC PPARγ mRNA and activity. These findings demonstrate that oxidative stress, potentially through activation of inhibitory redox-regulated transcription factors, attenuates PPARγ expression and activity in vascular endothelial cells through suppression of PPARγ transcription.